Sensitivity and specificity of CD19.CAR-T cell detection by flow cytometry and PCR - Schanda, Nicola; Sauer, Tim; Kunz, Alexander; Hückelhoven-Krauss, Angela; Neuber, Brigitte; Wang, Lei; Hinkelbein, Mandy; Sedloev, David; He, Bailin; Schubert, Maria-Luisa; Müller-Tidow, Carsten; Schmitt, Michael; et al. (Cells, 2021)
Chimeric-antigen-receptor-T (CAR-T) cells are currently revolutionizing the field of cancer immunotherapy. Therefore, there is an urgent need for CAR-T cell monitoring by clinicians to assess cell expansion and persistence in patients. CAR-T cell manufacturers and researchers need to evaluate transduction efficiency and vector copy number for quality control. Here, CAR expression was analyzed in peripheral blood samples from patients and healthy donors by flow cytometry with four commercially available detection reagents and on the gene level by quantitative polymerase chain reaction (qPCR). Flow cytometric analysis of CAR expression showed higher mean CAR expression values for CD19 CAR detection reagent and the F(ab’)2 antibody than Protein L and CD19 Protein. In addition, the CD19 CAR detection reagent showed a significantly lower median background staining of 0.02% (range 0.007-0.06%) when compared to the F(ab’)2 antibody, CD19 protein and Protein L with 0.80% (range 0.47-1.58%), 0.65% (range 0.25-1.35%) and 0.73% (range 0.44-1.23%). Furthermore, flow cytometry-based CAR-T cell frequencies by CD19 CAR detection reagent showed a good correlation with qPCR results. In conclusion, quality control of CAR-T cell products can be performed by FACS and qPCR. For the monitoring of CAR-T cell frequencies by FACS in patients, CAR detection reagents with a low background staining are preferable.
Gesehen am 01.04.2022